Breaking bad news: nursing perspective - Mirón González, R. (Revista Española de Comunicación en Salud, 2016)
Introduction: Braking bad news for health professionals has been one of the major challenges in recent decades. This is due to increased demand for information from patients and a sense of insecurity from the health professionals to address such communication. While the physician group was given the responsibility of breaking bad news, nursing began to be appreciated as a valuable piece that could be exploited. Aims: Identify the role of doctors and nurses on breaking bad news. Determine how to break bad news. Methodology: Literature review between 1999 and 2009. Results: Analysis of a total of 20 articles. Discussion: Nursing has increased importance into the breaking bad news in accordance with their great knowledge of the patients, even some authors who have come to argue that they are the ones who carry this communication out. Other authors support the breaking bad news like a multidisciplinary process that must be faced by those who have more information about the patient and their health. Various protocols have been found to address the breaking bad news: “SPIKES”, “ABCDE” and other methods. Conclusion: Breaking bad news is a multidisciplinary process where nursing is a key element which supports the patient and other professionals. But with the new changes, nursing is often required to initiate in breaking bad news, then they could benefit from the protocols that have been created for that purpose by other disciplines.